Internal motivation vs. learning environment support in EFL: evidence from students with diverse learning needs across four European countries - Karatsiori, Marianthi; Liontou, Trisevgeni; Domagala-Zysk, Ewa; Poredoš, Mojca; Košak Babuder, Milena; Vogt, Karin (Frontiers in Education, 2025)
This mixed-methods study explores the relationship between internal motivation and learning environment support in English as a Foreign Language (EFL) classrooms among students with diverse learning needs across four European contexts. Ninety-five students with visual, hearing, mobility impairments, or specific learning difficulties participated. Drawing on quantitative data from the Foreign Language Enjoyment Scale and qualitative interviews, the study examines how teacher support, peer collaboration, and technological tools shape learners’ experiences. While both teacher and peer support significantly predict internal motivation, the strength and nature of this relationship vary depending on the type of learning need. In particular, teacher support was most influential for students with visual impairments and learning difficulties, while peer support played a greater role for students with hearing and mobility support needs. Notably, students’ motivation often appeared to be independent of classroom-based support, with family encouragement emerging as a key informal driver. The study also identifies critical gaps in assistive technology training and access, with many students reporting limited instruction and inconsistent technical support. Students emphasized the need for accessible digital materials, flexible assessment strategies, and better-prepared teachers. Qualitative findings highlight preferences for structured environments, multimodal learning, and varied collaboration formats—individual, pair, or group—depending on students’ specific support needs and classroom contexts. These results point to the need for targeted teacher education, inclusive pedagogical design, and sustained systemic efforts to ensure equity in language learning for students with diverse profiles.